2019
DOI: 10.1080/14620316.2019.1628665
|View full text |Cite
|
Sign up to set email alerts
|

Diverse responsiveness of dehydrin genes to abscisic acid and water stress treatments in cucumber F1 cultivar hybrids

Abstract: View related articlesView Crossmark data Citing articles: 1 View citing articles Diverse responsiveness of dehydrin genes to abscisic acid and water stress treatments in cucumber F1 cultivar hybrids

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Specifically, the antibody binds to the k-segment peptide sequence (TGEKKGIMDKIKEKLPGQH) conserved in a wide range of different plant species. The reactivity of this antibody has also been confirmed in Solanum licopersicom L., as well as in other species such as Pistacia vera L. and Cucumis sativus L. [109][110][111].…”
mentioning
confidence: 62%
“…Specifically, the antibody binds to the k-segment peptide sequence (TGEKKGIMDKIKEKLPGQH) conserved in a wide range of different plant species. The reactivity of this antibody has also been confirmed in Solanum licopersicom L., as well as in other species such as Pistacia vera L. and Cucumis sativus L. [109][110][111].…”
mentioning
confidence: 62%
“…DHN2 was highly induced by both of the treatments. Moreover, transcription of DHN3 was moderately increased by the water deficit stress in the hybrids, while it was slightly responsive to ABA in all genotypes (Szegő et al, 2019). In addition, it was reported that SnRK2.10 (SNF-1 related protein kinase 2.10), which positively regulates signaling via ABA, could be related to phosphorylation of S-segments in DHNs (Vlad et al, 2008).…”
Section: Interaction With Phytohormonesmentioning
confidence: 95%